SITUS LIANGAN RAGAM DATA, KRONOLOGI, DAN ASPEK KERUANGAN - Sugeng Riyanto (Berkala Arkeologi, 2015)
The extensive early Mataram period (6th to 10th centuries A.D.) site of Liangan located on the slopes of the Sindoro volcano in Temanggung Regency has been under an ongoing long term research project by the Yogyakarta Archaeological Centre since 2009. This project will continue from 2015 until 2019. The first term of excavations has disclosed numerous important data relating to the age, extent and nature of the site as well as former environmental, geological and environmental data.Â Spatial aspects of this important Ancient Mataram site which covers an area of more than 5 hectares relate to former residential, sacral and agricultural activities. Well-preserved carbonized organic remains are an important feature of the site that reflect both agricultural and dietary features suggesting the impact of a volcanic eruption.